Sequential Reporting Bias - Aghamolla, Cyrus; Guttman, Ilan; Petrov, Evgeny (The Accounting Review, 2024)
ABSTRACT Firms with correlated fundamentals often issue reports sequentially, leading to information spillovers. The theoretical literature has investigated multifirm reporting, but only when firms report simultaneously. We examine the implications of sequential reporting, where firms aim to maximize their market price and can manipulate their reports. The introduction of sequentiality significantly alters the biasing behavior of firms and the resulting informational environment relative to simultaneous reporting. In particular, a lead firm always manipulates more when reports are issued sequentially. Moreover, relative to simultaneous reporting, sequential reporting reduces the overall information available to the market about each firm, resulting in less efficient and less volatile prices. Additionally, we find that stronger correlation in firm fundamentals can amplify the lead firm’s incentive for manipulation under sequentiality, in contrast to simultaneous reporting. We offer further results regarding, for example, market response coefficients, and provide a number of empirical implications. JEL Classifications: C72; D82; D83; G14; M41.